Self-reported hearing loss and cognitive impairment: a cross-sectional analysis of the EpiFloripa Aging study - Karina Mary de Paiva; Amanda Leticia Böell; Patrícia Haas; Alessandra Gianella Samelli; Danúbia Hillesheim; Thamara Hübler Figueiró; Eleonora d’Orsi (Cadernos de Saúde Pública, 2023)
This study aimed to investigate the association between self-reported hearing loss and cognitive impairment in older adults in a city in Southern Brazil. In this cross-sectional, population-based cohort study of older adults, data were collected in the third wave of the EpiFloripa Aging study (2017/2019), which had been performed since 2009 in the city of Florianópolis, Santa Catarina State. Cognitive impairment was the dependent variable analyzed by the Mini-Mental State Examination (MMSE), and self-reported hearing loss, which was included in the cohort only in the last wave, was the main exposure variable. Logistic regression analyses were conducted, considering the study design and sample weights. Data from 1,335 older adults were evaluated. The prevalence was 20.5% for cognitive impairment and 10.7% for hearing loss. Older adults with hearing loss were 2.66 (95%CI: 1.08-6.54) times more likely to have cognitive impairment than older adults without hearing loss. The association between hearing loss and cognitive impairment highlights the need to integrate the early identification of these problems into primary care, as both are risk factors for healthy aging and potentially preventable and/or treatable conditions.